Key activity areas of corporate social responsibility (CSR) in the construction industry: a study of China. (1st February 2016) - Jiang, Weiyan; Wong, Johnny K.W.
Abstract: China's ambitious urbanization continues to provide a strong impetus for the construction industry to proliferate in the foreseeable future. While construction firms are supposed to contribute extra efforts to improve social welfare, they are also attempting to minimize their negative impacts on the environment. This has compounded the difficulty of fulfilling corporate social responsibility (CSR), and it is vitally important that CSR activities can be formulated accordingly. In this study, generic CSR activities were identified first through extensive literature review. Content analysis on CSR reports of construction firms and interviews with professionals were then conducted to make the generic CSR activities suit the Chinese construction industry. A questionnaire survey was finally adopted to collect professionals' opinions on the importance of CSR activities. It is found that the key factors or activity areas of CSR are environmental protection, construction quality and safety, community, employees, clients, and CSR management. The research findings suggest that contractors' CSR fulfillment should be embedded in the construction process as well as the uniqueness of construction practices in China.